Celebrity-bashing or #MeToo contribution? New York Times Online readers debate the boundaries of hashtag feminism. Issue 1 (2nd January 2020) - Worthington, Nancy
ABSTRACT: In January 2018, a feminist blog, babe, detailed an anonymous woman's date with comedian Aziz Ansari, ending with her accusation that he had sexually assaulted her by escalating his sexual advances despite her verbal and nonverbal objections. Online reaction to the babe article was swift and plentiful, including a New York Times editorial written by conservative provocateur Bari Weiss entitled, "Aziz Ansari is Guilty. Of Not Being a Mind Reader." Weiss' piece drew 2953 online responses before the comment section closed the next day, with wide-ranging views addressing the respective behaviors and motivations of Ansari, "Grace, " and Weiss. The responses provide an opportunity to explore how commenters negotiate the boundaries of the #MeToo movement in the venue that had ignited the movement's resurgence with the story of movie mogul Harvey Weinstein's longstanding sexual abuse of women working in the film industry. This study applies quantitative and qualitative analysis to comment discourse and elicits three major themes: (1) expectations for seeking or conveying consent, (2) criteria for publicizing the private, and (3) demarcations between insensitivity and abuse. Justifications frequently offered for the positions articulated were based on references to personal experience, cultural expectations, the #MeToo movement, and feminism.